Ergonomic design and evaluation of visual coding for aircraft head-up display - Xu Xiao; Xiaoru Wanyan; Damin Zhuang; Zongmin Wei (2012 5th International Conference on Biomedical Engineering and Informatics, 2012)
It is a very important issue to design the head-up display's information display format appropriately, thus to help the pilot identify the targets and understand the external environment efficiently. The present study carries out the ergonomics design and evaluation of visual coding for aircraft head-up display based on the literature analysis. First, using the powerful OpenGL animation processing capability and VS2008 programming platform, the simulation model of aircraft head-up display layout and display are developed, and then the ergonomics experiment and evaluation method based on the operation performance test is designed. The experimental data processing results show that: the bar scale belt is superior to the curved scale belt; when a specific scale value is required, the belt scale display combined with a numeric box is superior to the belt scale display; when the blue sky is set as the background, the stroke width has a significant effect on the information identification; as the color coding of the abnormal messages, red is better than yellow but green is inappropriate; the aircraft symbol tested in the present study shows no insignificant effect on the information identification.